Mathematical Modelling of the Effects of Plasma Treatment on the Diffusivity of Biofilm - Tripti Thapa Gupta; Surya B. Karki; Ronald Fournier; Halim Ayan (Applied Sciences, 2018)
Biofilm formation on implanted medical devices is the reason for most of the nosocomial infections in clinical settings. Biofilms are more resistant to antimicrobials than their planktonic cells mainly because of the presence of the matrix of extracellular polymeric substances (EPSs), which acts as a physical barrier that limits the transport of antimicrobials inside the biofilm. A combinatorial antimicrobial approach of a non-thermal plasma and chlorhexidine (CHX) digluconate can be used to sterilize those surfaces contaminated with biofilm. However, the reason behind achieving this combinatorial decontamination is not known. Thus, in this study, we developed a mathematical model to explain the reason behind sterilization with the combinatorial treatment approach. It was found that the application of plasma prior to treatment with CHX is disrupting the biofilm and making it very porous. This is allowing CHX to penetrate deeper inside the porous biofilm, which is then effective at sterilizing the biofilm.